2016
DOI: 10.1371/journal.pone.0156133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Photoselective Vaporization versus Holmium Laser Enucleation for Treatment of Benign Prostate Hyperplasia in a Small Prostate Volume

Abstract: ObjectivePhotoselective vaporization of the prostate (PVP) using GreenLight and Holmium laser enucleation of the prostate (HoLEP) is an important surgical technique for management of benign prostate hyperplasia (BPH). We aimed to compare the effectiveness and safety of PVP using a 120 W GreenLight laser with HoLEP in a small prostate volume.MethodsPatients who underwent PVP or HoLEP surgery for BPH at our institutions were reviewed from May 2009 to December 2014 in this retrospective study. Among them, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…There is sufficient evidence for its efficacy comparable with TURP or open surgery. Men taking anti‐coagulants can be safely operated …”
Section: Treatmentmentioning
confidence: 99%
“…There is sufficient evidence for its efficacy comparable with TURP or open surgery. Men taking anti‐coagulants can be safely operated …”
Section: Treatmentmentioning
confidence: 99%
“…HoLEP success has been reproduced in a number of studies ( 11 ). Recently, some authors described similar results comparing HoLEP and 120W GL ( 12 , 13 ).…”
mentioning
confidence: 57%
“…However, Kim et al reported that there were no differences in the improvements of objective parameters in the comparison between PVP and HoLEP with a small prostate volume of less than 40 mL. 13 Enucleation of a large prostate results in forming a large cavity, which may therefore contribute to the improvement of objective parameters.…”
Section: Discussionmentioning
confidence: 99%